Employee Engagement and Organizational Citizenship Behavior Towards Subjective Well-Being of SLB Negeri Batu Merah Ambon Employee - Syafrianty Maruapey; Mohamad Arsad Rahawarin; Tehubijuluw Zacharias (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the influence of employee engagement and organizational citizenship behavior on subjective well-being of SLB Negeri Batu Merah Ambon employees. This study uses a quantitative approach with an associative method and a survey with a cross-section technique. The population used in this study were all SLB Negeri Batu Merah Ambon employees totaling 24 people. Determination of the number of saturated samples. Data were analyzed using multiple linear regression analysis. The results of the study concluded that (1) Employee engagement has an effect on Subjective Well-Being of SLB Negeri Batu Merah Ambon Employees; (2) Organizational citizenship behavior has an effect on Subjective Well-Being of SLB Negeri Batu Merah Ambon Employees; (3) Employee engagement and organizational citizenship behavior have an effect on Subjective Well-Being of SLB Negeri Batu Merah Ambon Employees